(3aJM GdbQjH GdeLjH Ydi GdJQZjH hGdJQgjHs - (3MSf Hf YdjGdajhej GdbGgQj, CHh Ydj,J (B870 (3g` s
(3ChdgG (B:s
(3CeQfG QShd Gddg Udi Gddg Ydjg hSde bGd UGMH GdYde GdeTghQ Ph GdfSHjf EPG bGd GdUMGHi CeQfG QShd Gddg Udi Gddg Ydjg hSde HcPG ChfgGfG Yf cPG s
(3BNQgG (B:s
(3jfJgi HUdGI GdESJNGQI Hbhdg (B: (3hjSei MGLJg Ci jYjf MGLI eKd Cf jbhd Ef cfJ JYde hcPG UQM GHf GdUdGM hGddg CYde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3ef JMHjS GdJGLQ GdMGL CHj GdYHGS CMeO Hf Ydi GdTQGjH Ydi GdTjN eMeO Hf YHO GdSdGe HfGfi hHYO GdGfbQGV jQLY Edi GdNRGfI GdbQhjjf s
(3fSNI ai SJI CLRGA s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdMOjK h GdeUWdMs